2004
DOI: 10.1128/iai.72.9.5506-5510.2004
|View full text |Cite
|
Sign up to set email alerts
|

Growth Phase Regulation of flaA Expression in Helicobacter pylori Is luxS Dependent

Abstract: LuxS plays a role in the synthesis of an extracellular signaling molecule, autoinducer 2 (AI-2). To analyze a possible role of AI-2 in regulating Helicobacter pylori gene expression, we constructed a panel of transcriptional reporter strains. We show that the expression of H. pylori flaA is growth phase dependent and that flaA transcription increases in association with increased culture density. Mutating the luxS gene eliminates growth-phase-dependent control of flaA, and this growth phase dependence is resto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 36 publications
(34 reference statements)
1
43
0
Order By: Relevance
“…Furthermore, in their studies, maximal accumulation of AI-2 in the culture occurred in stationary phase. It has also been reported that the expression of H. pylori flaA is growth-phase dependent (Thompson et al, 2003), and that flaA transcription increases with culture density (Loh et al, 2004) at stationary phase. Mutating the luxS gene eliminates the growth-phase dependence of flaA, and growth-phase dependence is restored when the luxS mutant is complemented with wild-type luxS.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, in their studies, maximal accumulation of AI-2 in the culture occurred in stationary phase. It has also been reported that the expression of H. pylori flaA is growth-phase dependent (Thompson et al, 2003), and that flaA transcription increases with culture density (Loh et al, 2004) at stationary phase. Mutating the luxS gene eliminates the growth-phase dependence of flaA, and growth-phase dependence is restored when the luxS mutant is complemented with wild-type luxS.…”
Section: Introductionmentioning
confidence: 88%
“…The present study is the first to show significantly reduced motility of the H. pylori luxS mutant. Recently, it has been shown that mutating the H. pylori luxS gene eliminates growth-phase-dependent control of flaA (Loh et al, 2004). …”
Section: Growth Of Luxs Mutantmentioning
confidence: 99%
“…Expression of early flagellar genes generally requires a transcriptional activator, referred to as the master regulator. While a master regulator has yet to be identified in H. pylori, some studies have shown that the quorum-sensing autoinducer synthase LuxS affects motility by altering expression of early and late flagellar genes (Loh et al, 2004;Osaki et al, 2006;Rader et al, 2007). The effect of LuxS on flagellar gene expression, however, is strainspecific (Joyce et al, 2000;Lee et al, 2006), and may be due to global changes in gene expression caused by decreased fitness in the luxS mutant rather than loss of quorum sensing (Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, AI-2 has been suggested to represent a widely distributed quorum-sensing signal that is recognized by many organisms (39). Inactivation of luxS has been reported to influence a wide variety of cellular processes, including type III secretion (43), cell motility (26,42), the development of biofilms (4,8,17,18,29,30,56), the expression of virulence factors (12,22,28), and iron uptake (11). The signal transduction mechanism that governs the cellular response to AI-2 has been most thoroughly characterized in Vibrio spp.…”
mentioning
confidence: 99%